SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN MEREK SMARTPHONE MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - Ade Kiki Fatmawati; Muhammad Sultan Raflie; Norma Yunita (STMIK Dian Cipta Cendikia Kotabumi, 2021)
Computers especially smartphones have experienced a very rapid development at this time. Both in terms of memory storage, battery and design and specifications are presented. Smartphones in its development undergoes a very rapid change. Many kinds of smartphone brands that offer all the advantages of a smartphone brand. Therefore the authers will examine and compare some of the criteria required smartphone students are expected with this writing and this research can add insight for anyone. The method used in this research is Analytical Hierarchy Process(AHP) method is very important approach in the selection of smartphone brand because the better quality of a brand of smartphone will arise satisfaction to student. In this study the outhors take four selection criteria, namely price, memory capacity, battery capacity and camera.